Implementation of Brown & Levinson’s Sociological Aspects in Verbal Interaction at Hotel Context - Rai Jaya Widanta, I Made; Budiarsa, Made; Simpen, I Wayan; Netra, I Made (e-Journal of Linguistics; Vol 11 No 2 (2017): eJL-July, 2017)
This research is an initiating reserach atempting to support the main project of developing pragmatic-based English teaching model at vocational college. Specifically, it is aimed examining whether (or not) sociocultural aspects of power, distance, and rank of imposition (PDR) proposed by Brown and Levinson (1987) is applicable for hotel context. In addition, it was aimed at designing oral role play card used for the main research data collecting. The role play card focuses on speech act (SA) of request and refusal. Twenty hotel staff were involved in doing exemplar generation, and activity undertaken to list situations at hotel dealing with request and refusal, and to inventory two most widely occured situation of each SA to be used as topic of role play card. The card was piloted by involving three students to see whether they were appropriate and obtain input of correction both content and language before being used. It was concluded that PDR is not tottaly suitable sosiological aspect used for criteria in doing verbal interaction at hotel context as power and distace (P D) are not distinctive aspects.